A Planning and Decision-Making Framework for Sustainable Humanitarian Logistics in Disaster Response - Oloruntoba, Richard (2015)
While the term sustainability has been used in a broad range of literatures, disciplines and contexts; sustainability in the context of humanitarian logistics (HL) has been given less attention and integration (Halldorsson and Kovacs 2010). Sustainable humanitarian logistics (SHL) planning and decision-making in response to natural disasters implies innovative, socially responsible, and proactive decision-making by logisticians that minimizes negative impacts, and enables long-term maintenance of community wellbeing, while maintaining a balance between social, environmental, and economic goals. This chapter outlines important assumptions from the existing literature on HL about its nature, processes and activities; and discusses unaddressed issues of environmental responsibility, community participation in disaster response and sustainability that are not currently addressed by the HL literature. Using case examples of natural disaster response and recovery, and associated logistical response in Australia as examples, the chapter illustrates the range and types of response and recovery-related logistical activities that contribute to sustainability in the field of HL, and from which a SHL planning and decision-making framework is proposed.